228k views
5 votes
What is a simpler form of the radical expression root36g^6

2 Answers

2 votes

Answer:

The simpler form of the radical expression
√(36g^6) is
6g^3.

Explanation:

To find the simpler form of the expression
√(36g^6).

Apply the radical rule
\sqrt[n]{ab}=\sqrt[n]{a}\sqrt[n]{b},\:\quad \mathrm{\:assuming\:}a\ge 0,\:b\ge 0


√(36)√(g^6)

We have that
√(36)=6, so
√(36g^6)=6√(g^6)

Next, apply the exponent rule
a^(bc)=\left(a^b\right)^c


g^6=g^(3\cdot \:2)=\left(g^3\right)^2


√(36)√(g^6)=6√(\left(g^3\right)^2)

Apply the radical rule
\sqrt[n]{a^n}=a,\:\quad \mathrm{\:assuming\:}a\ge 0


√(\left(g^3\right)^2)=g^3

Therefore,


√(36g^6)=6g^3

User Michael Defort
by
5.8k points
3 votes
we know that
√[36*g^6]
=√[6²*(g³)²]
=(√6²)*(√[(g³)²])
=6*g³

the answer is
6*g³
User StickyCube
by
5.9k points